2009
DOI: 10.1016/j.physc.2009.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic relaxation in pulse-magnetized high-temperature superconductors

Abstract: Abstract. A magnetic filed relaxation at the center of a pulse-magnetized single-domain Y-Ba Introduction.Textured high-temperature superconductors (HTS) of Re(Y)-Ba-Cu-O family appear to be very promising materials for manufacturing superconducting magnets with very large magnitudes of trapped magnetic fields [1,2]. For example, trapping a field as high as 17 T between two 26.5-mm diameter Y-Ba-Cu-O disks at 29K has been demonstrated recently [3]. A comprehensive review of synthesis, characteristics and appli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…It is wellknown that at lowering temperatures the relaxation rate suppressed exponentially [6]. In particular, when the temperature of the meltgrown samples in a liquid nitrogen changes by an amount θ , the relaxation rate varies as S = S 0 · e (−c·θ) (5) where S refers to the initial temperature, and c = 1.2 K −1 [13]. Actually, S depends weakly on the temperature; therefore, we assumed that it is equal to the isothermal relaxation measured at the liquid nitrogen temperature, so S 0 = S 78 .…”
Section: Numerical Computations and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is wellknown that at lowering temperatures the relaxation rate suppressed exponentially [6]. In particular, when the temperature of the meltgrown samples in a liquid nitrogen changes by an amount θ , the relaxation rate varies as S = S 0 · e (−c·θ) (5) where S refers to the initial temperature, and c = 1.2 K −1 [13]. Actually, S depends weakly on the temperature; therefore, we assumed that it is equal to the isothermal relaxation measured at the liquid nitrogen temperature, so S 0 = S 78 .…”
Section: Numerical Computations and Discussionmentioning
confidence: 99%
“…Moreover, it was found that the PFM method allows one to control not only the S magnitude, but also its sign. In some cases the increase of the trapper field over time was observed after the pulse magnetization [5]. It can be called "negative relaxation," according to the generally accepted definition of the relaxation [6].…”
Section: Introductionmentioning
confidence: 99%
“…Although the relaxation decay is mostly found to show a logarithmic time dependence [8], any decay may degrade the performance of superconducting magnetic devices, and finally involve potential influences on the operation stability. From this viewpoint, the magnetic relaxation phenomenon has aroused great attention of worldwide researchers and formed a crucial and intense topic accompanying the engineering applications of bulk HTS [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…(1) Импульсное намагничивание массивного сверхпроводника обычно протекает в адиабатических условиях, поскольку время теплообмена с термостатом значительно превышает длительность импульса. Вследствие этого величина захваченного поля в зависимости от амплитуды имеет узкий максимум [15]. В области температур T = 78 K захваченные поля при импульсном намагничивании примерно такие же, как в случае изотермического намагничивания.…”
unclassified